Pengaruh Green Innovation, Kebijakan Hutang, dan Keputusan Investasi Terhadap Kinerja Keuangan Perusahaan: Studi Kasus pada Perusahaan Pertambangan yang Terdaftar di BEI - M. Thegar Kahfi; Meily Surianti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to analyze the influence of Green Innovation, debt policy, and investment decisions on the financial performance of mining companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The study used a quantitative approach with a purposive sampling method, resulting in a sample of 44 companies based on the availability of financial reports and sustainability reports. The results show that Green Innovation has a negative and significant effect on financial performance (ROA). Debt policy, as measured by the Debt to Equity Ratio, has a negative and significant effect on financial performance, and investment decisions, as measured by Capital Expenditure to Book Value of Assets, have a positive and significant effect on financial performance. These findings suggest that mining companies should efficiently manage Green Innovation implementation costs, balance debt with equity financing, and strengthen strategic investment decisions in productive assets. Future research is recommended to consider additional variables such as dividend policy or company size and extend the observation period to capture long-term impacts.